La voz indio en textos americanos de 1494 a 1905 Un acercamiento gramatical a la historia conceptual - Company, Concepción Company (2019)
The paper analyzes the word indio and the concepts underlying it, in American documents from 1494 to 1905 written in Spanish. The paper examines the syntax, the semantics and the contexts in which indio appears, to shed light on the relationships between indio and other actors of the American society, like español, and to shed light on the conceptual changes along 400 years. The paper analyzes various independent syntactic and semantic variables; for instance, the general frequency of the word during four centuries, the textual genre in which indio preferably appears, the quantification, the individuation, and the semantic classes of verbs. In all variables, it is clear a strong social asymmetry for indio and the low social class status that indio had always in Spanish America. There are some important grammatical and conceptual changes in the 18th century.